Comparative Analysis of Long-Term Outcomes of Removable Plate Dentures and Implant-Supported Overdentures in Complete Edentulism - Musayeva, Hanife Hamdi (Actual Dentistry, 2026)
Treatment strategies for patients with complete edentulism must be guided by a highly individualized approach, as the condition of the edentulous oral cavity serves as a prognostic factor influencing both the complexity of prosthetic design and the expected treatment outcomes. Key considerations in managing such patients include the duration of edentulism and the patient’s adherence to regular dental visits, which are essential for the timely detection of potential complications following prosthetic rehabilitation. The aim of the study: was to conduct dynamic monitoring of quality indicators of removable prosthetic constructions in complete edentulism, including those supported by intraosseous implants. Materials and Methods: The study cohort comprised patients using conventional complete removable dentures and patients rehabilitated with overdentures retained by a bar supported on four implants. During the follow-up period, participants underwent professional oral hygiene procedures one to two times annually. Occlusal adjustment and denture retention control were performed as needed. The condition of the prostheses and supporting tissues was evaluated using 38 parameters. The principal indicators included frequency of use (continuous vs. intermittent for esthetics or mastication), insufficient retention, mismatch between the denture base and the supporting tissues, denture fracture, peri-implant gingival inflammation, and the necessity for denture remaking or replacement. Results: Insufficient retention of conventional complete dentures was first observed after one year of functional loading (5.7% of cases) and reached 100% after seven years. Similarly, progressive atrophy of the denture-bearing tissues was noted in 1.9% of cases after one year and in all cases after seven years. Conclusions: Over a seven-year observation period, the majority of conventional complete dentures required replacement due to insufficient retention, tissue atrophy, fractures, and wear of artificial teeth. Despite the inherent disadvantages of removable prostheses and the occurrence of peri-implant soft tissue inflammation, the overall quality indicator—defined as the need for replacement or modification of the prosthetic design—was significantly lower in implant-supported overdentures. These findings highlight the clinical advantages of overdentures compared with conventional complete removable dentures.